A Relational Perspective on Social Support Between Bereaved and Their Networks After Terror: A Qualitative Study. (August 2018) - Dyregrov, Kari; Kristensen, Pål; Dyregrov, Atle
The aim of this study is to increase the understanding of social network support after traumatic deaths and, by demonstrating the complexities of such encounters, to highlight whether such support may be totally beneficial. A phenomenological dynamic and relational perspective was applied to 22 in-depth interviews with parents bereaved as a result of the 2011 terror attack in Norway. Three main themes were identified in respect of interactional support processes: (a) valued support, (b) stressful experiences, and (c) interactive barriers. As well as describing the value of experienced support, the article also elaborates on the effect of lacking, avoidant, and inept support. The findings show that insecure communication and a nonmatching understanding of time and emotional overload can form interactive barriers between the bereaved and their networks. By better understanding the relational regulation processes inherent in social support we may provide informed advice to both the bereaved and their networks to maximize recovery.